2006
DOI: 10.1213/01.ane.0000197779.03866.ad
|View full text |Cite
|
Sign up to set email alerts
|

Successful Intraoperative Use of Recombinant Tissue Plasminogen Activator During Liver Transplantation Complicated by Massive Intracardiac/Pulmonary Thrombosis

Abstract: During orthotopic liver transplantation a patient received epsilon-aminocaproic acid and clotting factors. Shortly after hepatic artery clamping the patient developed a massive intracardiac/intravascular thrombosis that resulted in cardiac arrest. After diagnosis by transesophageal echocardiography, the patient was treated with recombinant tissue plasminogen activator through a central venous catheter advanced into the right atrium. After treatment with recombinant tissue plasminogen activator, the patient's h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 24 publications
0
45
0
Order By: Relevance
“…4,7,9,10,12,13,17,18 Others are inherent to the OLT procedure: excessive activation of the coagulation system, venous stasis during clamping of the portal vein and inferior vena cava, and release of activators from the liver graft. 6,7,9 In addition, other conditions such as heparin-induced thrombocytopenia, factor V Leiden, and antithrombin deficiency can contribute to thrombosis and possibly ICTs during OLT. Finally, intraoperative management may play an important role: PA catheter placement; the administration of antifibrinolytics, anti-hepatitis B immunoglobulin, and blood products; and the intraoperative utilization of continuous venovenous filtration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,7,9,10,12,13,17,18 Others are inherent to the OLT procedure: excessive activation of the coagulation system, venous stasis during clamping of the portal vein and inferior vena cava, and release of activators from the liver graft. 6,7,9 In addition, other conditions such as heparin-induced thrombocytopenia, factor V Leiden, and antithrombin deficiency can contribute to thrombosis and possibly ICTs during OLT. Finally, intraoperative management may play an important role: PA catheter placement; the administration of antifibrinolytics, anti-hepatitis B immunoglobulin, and blood products; and the intraoperative utilization of continuous venovenous filtration.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, intraoperative management may play an important role: PA catheter placement; the administration of antifibrinolytics, anti-hepatitis B immunoglobulin, and blood products; and the intraoperative utilization of continuous venovenous filtration. 2,4,7,8,[10][11][12][13][14][18][19][20] Risk factor analysis for ICTs during OLT has proved to be difficult because of the relatively low incidence. In this study, we showed that symptomatic and/or surgically treated portal hypertension and intraoperative hemodialysis were independent risk factors for the development of incidental ICTs during OLT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infectious conditions, however, are a well-defined and strong risk factor for thrombotic events, and this effect may last for weeks after the septic episode [55,56]. Other suggested risk factors are certain drugs and blood products, such as hepatitis B immunoglobulin [24,31,34], the combination of aprotinin and octreotide [37], solvent-detergent plasma [36], and large volumes of cryoprecipitate, fresh frozen plasma or platelet concentrates [20,21,23]. The potential role of acquired and congenital thrombophilia disorders, such as protein C, protein S, or antithrombin III deficiencies or factor (F) V Leiden mutation, has been investigated in only a small number of patients [17,27,29,32].…”
Section: Discussionmentioning
confidence: 99%
“…The most frequently described risk factors were venovenous bypass [13,15,18,[23][24][25]29,30,32,[34][35][36][38][39][40]45] and the use of antifibrinolytic medication [13,17,19,21,23,25,26,[28][29][30][31][32][34][35][36][37][38][39][42][43][44]. However, PE and ICT have been reported in almost an identical number of patients with or without these two putative risk factors (Table 3).…”
Section: Putative Risk Factorsmentioning
confidence: 99%